Safety and efficacy of minimally invasive surgery plus alteplase in intracerebral haemorrhage evacuation (MISTIE): a randomised, controlled, open-label, phase 2 trial. Issue 12 (November 2016) - Hanley, Daniel F; Thompson, Richard E; Muschelli, John; Rosenblum, Michael; McBee, Nichol; Lane, Karen; Bistran-Hall, Amanda J; Mayo, Steven W; Keyl, Penelope; Gandhi, Dheeraj; Morgan, Tim C; Ullman, Natalie; et al.
Summary: Background: Craniotomy, according to the results from trials, does not improve functional outcome after intracerebral haemorrhage. Whether minimally invasive catheter evacuation followed by thrombolysis for clot removal is safe and can achieve a good functional outcome is not known. We investigated the safety and efficacy of alteplase, a recombinant tissue plasminogen activator, in combination with minimally invasive surgery (MIS) in patients with intracerebral haemorrhage. Methods: MISTIE was an open-label, phase 2 trial that was done in 26 hospitals in the USA, Canada, the UK, and Germany. We used a computer-generated allocation sequence with a block size of four to centrally randomise patients aged 18–80 years with a non-traumatic (spontaneous) intracerebral haemorrhage of 20 mL or higher to standard medical care or image-guided MIS plus alteplase (0·3 mg or 1·0 mg every 8 h for up to nine doses) to remove clots using surgical aspiration followed by alteplase clot irrigation. Primary outcomes were all safety outcomes: 30 day mortality, 7 day procedure-related mortality, 72 h symptomatic bleeding, and 30 day brain infections. This trial is registered withClinicalTrials.gov, numberNCT00224770 . Findings: Between Feb 2, 2006, and April 8, 2013, 96 patients were randomly allocated and completed follow-up: 54 (56%) in the MIS plus alteplase group and 42 (44%) in the standard medical care group. The primary outcomes did not differ between the standard medical care and MIS plus alteplase groups: 30 day mortality (four [9·5%, 95% CI 2·7–22.6] vs eight [14·8%, 6·6–27·1], p=0·542), 7 day mortality (zero [0%, 0–8·4] vs one [1·9%, 0·1–9·9], p=0·562), symptomatic bleeding (one [2·4%, 0·1–12·6] vs five [9·3%, 3·1–20·3], p=0·226), and brain bacterial infections (one [2·4%, 0·1–12·6] vs zero [0%, 0–6·6], p=0·438). Asymptomatic haemorrhages were more common in the MIS plus alteplase group than in the standard medical care group (12 [22·2%; 95% CI 12·0–35·6] vs three [7·1%; 1·5–19·5]; p=0·051). Interpretation: MIS plus alteplase seems to be safe in patients with intracerebral haemorrhage, but increased asymptomatic bleeding is a major cautionary finding. These results, if replicable, could lead to the addition of surgical management as a therapeutic strategy for intracerebral haemorrhage. Funding: National Institute of Neurological Disorders and Stroke, Genentech, and Codman.